Tiga Pilar Pengendalian Hipertensi Berbasis Komunitas: Edukasi Pasien, Penguatan Kader, dan Pelatihan Petugas Puskesmas : Indonesia - Rahmawati, Riana; Fauziyati, Ana; Widayati, sri; Nazihah, Nida Zahrotun; Natasya, Alma (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
Hypertension control in primary care remains a public health challenge in Indonesia. Among pre-elderly and older adults, hypertension prevalence is higher, increasing the risk of serious cardiovascular complications. Sustained strengthening is required for comprehensive initiatives that engage both health professionals and community health workers (cadres). This community service program aimed to enhance the roles of patients, elderly posyandu cadres, and the puskesmas staff in hypertension management in  Pandak Village, Bantul Regency. The methods and approaches included case mapping, community-based screening, cadre training, provision of tensimeters, patient/family education, and training for puskesmas health workers. Data from the puskesmas indicated that 355 Pandak residents had hypertension. Community screening targeting pre-elderly and older adults was attended by 186 residents, of whom 154 were confirmed to have hypertension. Cadre training involved 12 elderly posyandu cadres, focusing on how to conduct elderly screening (anthropometry and blood pressure check) and interpret hypertension status. Before the training, only two cadres were able to measure blood pressure using tensimeter, whereas after the training all attending cadres were able to perform measurements independently. The program also provided seven sets of tensimeters to improve access to blood pressure monitoring in Pandak Village. Training for puskesmas health workers on “Current Hypertension Therapy and Its Implementation in Primary Care” was attended by 21 participants (doctors, nurses, and midwives). Knowledge increased, with the mean pre-test score rising from 61.0 to 83.8 in the post-test. Overall, the program enhanced the capacity of cadres and puskesmas staff and improved access to hypertension screening and monitoring.